Răspuns :
a) L=3*l
P=2(L+l)=2*4l=8l=32m ===> l=4m====>L=12m
b)P=8l=64m====>l=8m====>L=24m
P=2(L+l)=2*4l=8l=32m ===> l=4m====>L=12m
b)P=8l=64m====>l=8m====>L=24m
L= 3 x l
L- lungimea
l- latimea
a) P = 32 m stiind ca L = 3 x l , atunci
P = 2 x L + 2 x l
P = 2 x 3l + 2 x l
P = 8 l
l = 32 : 8
l = 4
L= l x 3
L= 4x3
L=12
B)
L= 3 x l
P = 2 x 3l + 2 x l
P = 64
P = 8 l
l = 64 : 8
l = 8
L = 8 x 3
L = 24
Spor la scoala ;)
L- lungimea
l- latimea
a) P = 32 m stiind ca L = 3 x l , atunci
P = 2 x L + 2 x l
P = 2 x 3l + 2 x l
P = 8 l
l = 32 : 8
l = 4
L= l x 3
L= 4x3
L=12
B)
L= 3 x l
P = 2 x 3l + 2 x l
P = 64
P = 8 l
l = 64 : 8
l = 8
L = 8 x 3
L = 24
Spor la scoala ;)